The new era of capital regulation complexity - Lukáš Pfeifer (Journal of Central Banking Theory and Practice, 2023)
The paper describes the mechanism of overlapping lever-age ratio requirement and macroprudential capital buffers and as-sociated implications for the resilience of the banking sector. It ex-amines to what extent capital buffers can be usable to absorb lossesin the case of the Czech banking sector and what impact this mayhave on the lending capacity of the real economy. The non-usabilityportion of capital buffers in the Czech banking sector amounts toCZK 27 billion (i.e. 24% of the combined capital buffer). The lend-ing potential of the capital buffer decreases by CZK 630 billion toCZK 1.6 trillion due to overlaps under otherwise equal conditions.The results indicate that the leverage ratio requirement may preventthe capital buffers from being fully effective and can reduce createdmacroprudential space.
Keywords: G21; G28; E58; 330; capital ratio requirement; leverage ratio requirement; overlaps; capital buffers